2020
DOI: 10.1016/j.clnu.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of physical activity and sedentary behavior on body composition in university students

Abstract: Background & aims: This study aimed to evaluate the domain-specific physical activity (PA) levels and sitting time of a sample of university students and examine the association of PA with percent body fat. Methods: Two hundred and twenty-one students were included in the analysis. We administered the long form of the International Physical Activity Questionnaire (IPAQ) twice within one-month interval. Total PA as well as occupational, transportation-, housework-, and leisure-related PA were assessed, in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Pese a que los resultados indican que los sujetos con una composición de masa grasa más saludable tienen una menor probabilidad de alcanzar los niveles de AF recomendados, las pruebas de correlación entre el %MG y la AFT muestran una relación inversa y no significativa. Esto último estaría en consonancia con la relación inversa y de baja a moderada cuantía informada en diversos estudios entre la composición grasa y la AFM (Harmouche-Karaki, et al, 2020), la AF habitual (Gamarra, et al, 2021;Gómez, Ceballos, & Enríquez, 2018;Rangel, Rojas, & Gamboa, 2015;Ruchan, 2015;Serpa, et al, 2017;Zulet, et al, 2019) o la AFT (Wanner, et al, 2016;Zaccagni, Barbieri, & Gualdi, 2014). Aunque también hay estudios que no demuestran dicha relación (Castro, et al, 2018) o que indican que los estudiantes con peso normal (Meseguer, et al, 2009) y sobrepeso tienen más probabilidades de alcanzar los niveles de AF recomendados que aquellos con bajo peso y obesos (Acebes-Sánchez, et al, 2019;Scarapicchia, Sabiston, & Faulkner, 2015).…”
Section: Discussionunclassified
“…Pese a que los resultados indican que los sujetos con una composición de masa grasa más saludable tienen una menor probabilidad de alcanzar los niveles de AF recomendados, las pruebas de correlación entre el %MG y la AFT muestran una relación inversa y no significativa. Esto último estaría en consonancia con la relación inversa y de baja a moderada cuantía informada en diversos estudios entre la composición grasa y la AFM (Harmouche-Karaki, et al, 2020), la AF habitual (Gamarra, et al, 2021;Gómez, Ceballos, & Enríquez, 2018;Rangel, Rojas, & Gamboa, 2015;Ruchan, 2015;Serpa, et al, 2017;Zulet, et al, 2019) o la AFT (Wanner, et al, 2016;Zaccagni, Barbieri, & Gualdi, 2014). Aunque también hay estudios que no demuestran dicha relación (Castro, et al, 2018) o que indican que los estudiantes con peso normal (Meseguer, et al, 2009) y sobrepeso tienen más probabilidades de alcanzar los niveles de AF recomendados que aquellos con bajo peso y obesos (Acebes-Sánchez, et al, 2019;Scarapicchia, Sabiston, & Faulkner, 2015).…”
Section: Discussionunclassified
“…At the same time, different departments, schoolwork pressure and participation in leisure activities will also affect body composition ( 16 ). Studies have shown that high body fat, insufficient muscle mass and physical weakness can induce the risk of juvenile sarcopenia and obesity ( 17 ). Obesity can be caused by excessive body fat and obesity can cause comorbidify such as diabetes, hypertension, hyperlipidemia and mental disorders (such as social impairment and depression) ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This popular technology has shown high agreement with the gold-standard dual energy X-ray absorptiometry (DXA) [ 12 , 13 ] in the past few years. It has also been used to evaluate the nutritional status of some populations, including college students [ 14 ]. Fat mass index (FMI) and fat-free mass index (FFMI) indices eliminate the differences of body fat percentages associated with height, which could be useful for the measurement of related body composition [ 15 ].…”
Section: Introductionmentioning
confidence: 99%